The Role of Public Accountants in Preventing and Detecting Fraud in PT Kimia Farma's Financial Reports - Silalahi, Yesy Dinauli; Munte, Mestika; Lubis, Yunita; Aldira, Hasvia Sheila; Rizkina, Miftha (EDUCTUM: Journal Research, 2025)
Using the 2001 PT Kimia Farma financial reporting scandal as a case study, this study aims to analyze the role of public accountants in preventing and detecting financial reporting fraud. This scandal attracted public attention because it revealed revenue manipulation amounting to Rp32.6 billion, which caused the financial reports to misrepresent the company's true financial condition. This research was conducted qualitatively through a case study and supported by literature analysis with relevant documents. The results show that the role of public accountants is not ideal in this situation, especially in terms of applying professional skepticism and strict audit procedures. The failure to identify fraud at the audit stage demonstrates the importance of improving audit quality, understanding fraud risks, and implementing stricter audit standards. These findings have significant consequences for the accounting profession, especially in terms of developing more effective methods for preventing and detecting fraud in an effort to maintain the credibility of financial reporting and public trust.